Pharmacognostic evaluation with reference to catechin content and antioxidant activities of pale catechu in Thailand - Thidarat Duangyod; Chanida Palanuvej; Nijsiri Ruangrungsi (Wolters Kluwer Medknow Publications, 2015)
Pale catechu, a well-known crude drug, has been widely used for anti-diarrhea. Due to its medicinal usage, this study was performed to evaluate the pharmacognostic and antioxidant properties as well as catechins contents of pale catechu in Thailand. Twenty samples of pale catechu collected from traditional drug stores throughout Thailand were investigated. Antioxidant activities, total phenolic, nontannin phenolic, and total tannin contents were evaluated. (+)-catechin and (−)-epicatechin were quantitatively analyzed by high performance liquid chromatography. The results revealed that most of pale catechu samples were adulterated according to high ash values. Qualified pale catechu in Thailand were demonstrated for their average contents of total ash, acid insoluble ash, loss on drying, and moisture as 5.20 ± 0.19, 1.61 ± 0.17, 13.14 ± 0.10, and 13.20 ± 1.07 g/100 g of dry weight, respectively. The ethanol and water soluble extractive matters were 91.66 ± 5.16 and 44.59 ± 3.18 g/100 g of dry weight respectively. (+)-catechin in theses samples was 478.87 ± 2.77 μg/mg of crude drug, whereas (−)- epicatechin was found to be trace (< limit of quantitation). The promising antioxidant activities were demonstrated compared to (+)- catechin hydrate.